Factors Causing Delay in Return of Medical Record Files of Inpatients - Desmita Rahmadhani; Zulfa Zulfa; Dessy Angraini (GLOBAL HEALTH SCIENCE GROUP, 2025)
The purpose of the study was to determine the factors causing the delay in returning inpatient medical record files. This study used a qualitative approach with observation and interview methods. The factors causing the delay were human resource factors, lack of compliance and discipline of doctors and nurses in filling out medical records, uncertainty of doctor's visiting hours and DPJP not being a permanent doctor. Infrastructure factors, namely medical record forms are not always available in the inpatient room. The method factor is that there is no written SOP for filling out medical records. The policy factor is that there is no reward and punishment for filling out inpatient medical records.